2023
DOI: 10.3389/fonc.2023.1167567
|View full text |Cite
|
Sign up to set email alerts
|

HER2-low metastases of HER2-negative primary tumors: a single institution analysis of intertumoral and internodal heterogeneity in node-positive breast cancer

Abstract: ObjectiveHER2 status in breast cancer is an essential parameter in individual therapeutic decision-making and is routinely assessed in primary tumors in accordance with international recommendations. Reports of HER2 heterogeneity raise the question of basing treatment decisions on HER2 status in metastases, if present. We investigated the degree and clinical implications of HER2 heterogeneity in lymph node–positive breast cancer. Because of recent recognition of therapeutic opportunities in this group of tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Discrepancies in biomarker profiles may reflect differences in clonal tumor populations and then influence the response to the available therapeutic regimens. Several works have focused on the different patterns of biomarker expression between primary BCs and synchronous ALN metastases in surgical specimens [10][11][12][13][14][15][16]. Although with variable rates, discordances in the biomarker profile between PTs and ALNs have emerged, such as hormone-sensitive tumors with negative metastases [10,11] or HER2-negative breast neoplasms with overexpression/FISH amplification in lymph nodes [13,14], among others.…”
Section: Introductionmentioning
confidence: 99%
“…Discrepancies in biomarker profiles may reflect differences in clonal tumor populations and then influence the response to the available therapeutic regimens. Several works have focused on the different patterns of biomarker expression between primary BCs and synchronous ALN metastases in surgical specimens [10][11][12][13][14][15][16]. Although with variable rates, discordances in the biomarker profile between PTs and ALNs have emerged, such as hormone-sensitive tumors with negative metastases [10,11] or HER2-negative breast neoplasms with overexpression/FISH amplification in lymph nodes [13,14], among others.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several retrospective studies have reported inconsistent biomarkers, i.e. estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor-2 (HER2), between the primary lesions and metastases of breast cancer (3)(4)(5)(6). The majority of the discordance occurred only one or two of ER, PR and HER2 status.…”
Section: Introductionmentioning
confidence: 99%